Dietary Inflammatory Potential Is Associated With Sarcopenia Among Chronic Kidney Disease Population - Huang, Ying; Zeng, Mengru; Zhang, Lei; Shi, Jingzheng; Yang, Yuan; Liu, Fuyou; Sun, Lin; Xiao, Li (Frontiers in Nutrition, 2022)
Background Sarcopenia, characterized by impaired muscle mass and function, is a common complication and main reason for bad life quality and high mortality in chronic kidney disease (CKD). Limiting systemic inflammation is a potable intervention for sarcopenia. Dietary inflammatory potential can influence systemic inflammation. However, research about the association between dietary inflammatory potential and sarcopenia in CKD is limited. Aim To investigate the association between dietary inflammatory potential and sarcopenia in CKD population. Methods We conducted a cross-section study based on public database National Health and Nutrition Examination Survey (NHANES). 2569 adult CKD participants who had complete data for dietary inflammatory potential and sarcopenia were included. Dietary inflammatory potential was calculated by dietary inflammation index (DII) score based on dietary recall interviews. We assessed sarcopenia via low skeletal muscle mass measured by dual energy x-ray absorptiometry. Smooth curve fitting and generalized linear mixed model were used to evaluate the relationship between DII and sarcopenia. Subgroup and sensitive analysis were also performed. Results The overall prevalence of sarcopenia among CKD patients is 19.11%. Smooth curve fitting results displayed DII score is near linear positively associated with sarcopenia. Logistic regression confirmed sarcopenia is independently related with DII scores (OR, 1.17; 95%CI, 1.06-1.29). Subgroup analyses revealed relatively stronger associations between DII and sarcopenia among CKD patients with other sarcopenia risk factors, including hypoalbuminemia, low energy intake, low protein intake and comorbidities. Conclusion Dietary inflammatory potential is independently related with sarcopenia among CKD patients. Anti-inflammatory diet patterns may be a protective intervention for CKD associated sarcopenia.